- Title: Title: Serum Ceramide Species and Meteorin-Like Protein as a Novel Combined Biomarker Panel for the Diagnosis of Early-Stage Type 2 Diabetes Mellitus: Novel Combined Biomarker Panel for the Diagnosis of Early-Stage Type 2 Diabetes Mellitus - Zhao , Xiaoyu; Pulatov , Muhriddin; Kurbanova , Shakhlokhon (Journal of Medical Biochemistry, 2026)
Background: The identification of biomarkers reflecting early pathophysiological changes in Type 2 Diabetes Mellitus (T2DM) is crucial for timely intervention. Ceramides, lipotoxic sphingolipids, and Meteorin-like protein (Metrnl), an insulin-sensitizing adipomyokine, are mechanistically linked to T2DM development. Aims: To compare serum levels of specific ceramides (Cer-16, Cer-18, Cer-24, Cer-24:1) and Metrnl between T2DM patients and controls, and to evaluate their individual and combined diagnostic accuracy. Methods: This case-control study included 80 newly diagnosed T2DM patients and 80 age- and BMI-matched normoglycemic controls. Fasting serum was analysed for standard biochemical parameters. Ceramide species were quantified by LC-MS/MS. Serum Metrnl was measured via ELISA. Results: The T2DM group exhibited significantly elevated levels of Cer-16 (p<0.001) and Cer-18 (p<0.01), and reduced levels of Cer-24 and Metrnl (both p<0.001). The Cer-16/Cer-24 ratio was significantly higher in T2DM. Strong correlations were found between these biomarkers and HOMA-IR/HbA1c. A multivariate logistic regression model combining Cer-16, Cer-24, and Metrnl yielded an AUC of 0.93 for T2DM discrimination, superior to any single marker. Conclusions: A distinct ceramide profile (high Cer-16, low Cer-24) coupled with low Metrnl characterizes early T2DM. Their combination forms a synergistic biomarker panel with high diagnostic potential, mirroring the dual pathology of lipotoxicity and impaired metabolic protection.